2011
DOI: 10.1186/1471-2458-11-904
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the costs of induced abortion in Uganda: A model-based analysis

Abstract: BackgroundThe demand for induced abortions in Uganda is high despite legal and moral proscriptions. Abortion seekers usually go to illegal, hidden clinics where procedures are performed in unhygienic environments by under-trained practitioners. These abortions, which are usually unsafe, lead to a high rate of severe complications and use of substantial, scarce healthcare resources. This study was performed to estimate the costs associated with induced abortions in Uganda.MethodsA decision tree was developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 25 publications
(33 reference statements)
0
30
0
1
Order By: Relevance
“…11 Using Monte Carlo methods, a Ugandan study estimated that the average woman pays US$62 per abortion in direct costs, including those for any postabortion care. 14 However, very few studies have looked at the social and economic impact of unsafe abortion on women and their households. A study in Cambodia examined the number of days lost from a woman's normal routine, as well as the wages lost by the woman and her family members because of need for postabortion care and continuing morbidity from the abortion.…”
mentioning
confidence: 99%
“…11 Using Monte Carlo methods, a Ugandan study estimated that the average woman pays US$62 per abortion in direct costs, including those for any postabortion care. 14 However, very few studies have looked at the social and economic impact of unsafe abortion on women and their households. A study in Cambodia examined the number of days lost from a woman's normal routine, as well as the wages lost by the woman and her family members because of need for postabortion care and continuing morbidity from the abortion.…”
mentioning
confidence: 99%
“…This baseline analysis of health-related quality of life and social support utilizes data from a prospective cohort study to evaluate the impact of abortion complications on health and economic outcomes of women in Uganda [2,10]. Between December 2009 and October 2010, we enrolled women at discharge who had been admitted to the Obstetric and Gynecology unit for treatment of complications resulting from induced abortions.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies in Uganda have documented the substantial economic costs associated with unsafe abortions and resulting complications. Babigumira et al [2], using a decision-analytic model to represent the consequences of an induced abortion, estimated an annual per-patient societal cost of $171, translating into $64 million in costs per year for the country. In an empirical analysis, Vlassoff et al [3] found that the annual cost of treating abortion complications was approximately $131 per case and $13.9 million per year in Uganda, and an estimated $20.8 million per year that would be needed to satisfy all demand for management of abortion complications in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers who unintentionally become pregnant opt for unsafe abortions due to the insufficiency and inaccessibility of safe abortion services, restrictive laws, high costs, and diligent objections by health care providers who observe the professional ethic of do not harm and due to insufficient knowledge of eligibility for safe abortion care . Nonetheless, in Asia and Europe, older women procure abortion mainly to limit or space births .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents from African countries may particularly pursue abortions because of probable consequences such as stigmatization . It is often procured through clandestine measures and in unhygienic hidden places, offered by untrained practitioners . These abortions are generally unsafe, accounting for 21% of the maternal deaths that occur annually, making it an issue of public health importance in the region.…”
Section: Introductionmentioning
confidence: 99%